Corruption Reduction in the Petroleum Sector in Nigeria: Challenges and Prospects - Obioma, Benneth K. (Richtmann Publishing, 2012)
Corruption, in any way it is looked at, is a social-cankeworm as it pays no person, party government,institution and the society any good. Corruption is manifested in every phase and sector of the Nigeriansocio-political economy but it is more pronounced in the petroleum sector in the country. Because Nigeriaso much depends on the petroleum sector as her sources of living, income, economic growth anddevelopment, any corrupt practice in the sector by any person or party automatically affects all othersectors of the economy. Efforts have been made by both the past and present governments throughlegislative, executive and legal frameworks as well as administrative; to reduce corruption in the sector butit seems that not much has been achieved to drastically reduce this social vice in the Nigerian society. It istherefore suggested here that a combined effort of all stakeholders in the oil and gas business – the federaland state governments, the judiciary, legislature, law enforcement agencies (the ICPC, EFCC, immigration,customs, police, army, air force, navy, civil defence corps, etc) as well as the Nigeria National PetroleumCorporation (NNPC), the oil multinational companies in Nigeria, the oil markets and internationalcommunity and other agencies like UNDP, World Bank, IMF, etc- should be the only way out to wipecorruption out of the country. The only way is through transparency and proper accountability in alldealing in the sector.